1999
DOI: 10.1039/a807981a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of Pt and I by ICP-MS for studies of the mechanism of reaction of diiodoplatinum anticancer complexes

Abstract: The determination of Pt by ICP-MS in environmental and biological samples is well documented and generally performed after dissolution in dilute HNO 3.On the other hand, I is poorly ionised in the plasma and, at low pH, memory effects and instability arise from the formation of potentially volatile species, such as I 2 and HI, depending on the oxidation state of I. In order to investigate the role of iodo ligands in the design of Pt anticancer complexes, we have optimised conditions for the simultaneous determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Comparatively, studying the time course of the reaction of [Pt(en)I 2 ] 25 and the chloro-analogue 22 revealed that the diiodo complex reacts more rapidly with albumin but by the authors' observations gives no products with Pt coordinated to cysteine-34 . As another part of current work on the role of iodo ligands in the design of platinum anticancer complexes, the distribution of Pt and I among high and low M w fractions at different stages of the reaction of 24 and 25 with human albumin was investigated by ICP-MS. , The determination of the Pt/I ratio in the low M w fraction of reaction mixtures separated by ultrafiltration provided evidence for different kinetics for the albumin-binding reactions of diiodo Pt(II) and Pt(IV) complexes and for the release of iodide at an early stage of the reaction. Kratochwil and Bednarski explored a wider range of Pt(IV)−ethylenediamine complexes with the general formula [Pt(en)X 2 Y 2 ] (X = Cl; Y = Cl, OH, OCOCH 3 ; X = I; Y = Cl, OH, OCOCH 3 , OCOCF 3 , OSO 2 CH 3 ) with respect to the rate of their reduction by bovine serum albumin.…”
Section: 4 Other Platinum Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparatively, studying the time course of the reaction of [Pt(en)I 2 ] 25 and the chloro-analogue 22 revealed that the diiodo complex reacts more rapidly with albumin but by the authors' observations gives no products with Pt coordinated to cysteine-34 . As another part of current work on the role of iodo ligands in the design of platinum anticancer complexes, the distribution of Pt and I among high and low M w fractions at different stages of the reaction of 24 and 25 with human albumin was investigated by ICP-MS. , The determination of the Pt/I ratio in the low M w fraction of reaction mixtures separated by ultrafiltration provided evidence for different kinetics for the albumin-binding reactions of diiodo Pt(II) and Pt(IV) complexes and for the release of iodide at an early stage of the reaction. Kratochwil and Bednarski explored a wider range of Pt(IV)−ethylenediamine complexes with the general formula [Pt(en)X 2 Y 2 ] (X = Cl; Y = Cl, OH, OCOCH 3 ; X = I; Y = Cl, OH, OCOCH 3 , OCOCF 3 , OSO 2 CH 3 ) with respect to the rate of their reduction by bovine serum albumin.…”
Section: 4 Other Platinum Complexesmentioning
confidence: 99%
“…Regarding the determination of Pt in the presence of protein material, it should be noted that Sadler and co-workers were the first who demonstrated that ICP-MS with direct injection nebulization holds great promise to precisely measure Pt concentrations (down to 0.03 μg L -1 ) . Moreover, the capability of ICP-MS for multielement detection with an almost unrivaled sensitivity is of particular interest for investigations of the functions of transport proteins with affinity for more than one element (e.g., transferrin or metallothionein) and studies on the mechanism of action for newly designed drugs involving metal centers …”
Section: 4 Other Platinum Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Plasma Quad 3 instrument (VG Elemental, Winsford, U.K.), equipped with the S-option for increased sensitivity, was used for all measurements. Details of the procedure used for the simultaneous determination of Pt and I on the high and low M r fractions by ICP-MS are reported elsewhere . Briefly, Pt complexes were incubated with either rHA or NEM-rHA at a molar ratio of 1:1 (100 μM) in 100 mM NaCl, 10 mM NaH 2 PO 4 , pH 7.4, at 310 K for 24 h. The binding of I - to albumin was assessed independently by incubating KI (200 μM) with rHA for 24 h in a 1:2 molar ratio.…”
Section: Methodsmentioning
confidence: 99%